Production Process of D-Nose Panel Components for A-350 Airplane Wings, PT Dirgantara Indonesia - Brilliant Yosef Pandapotan; Dodi Sofyan Arief; Sarmaini Fridawaty; Firdaus M (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2023)
Airplanes are one of the most frequently used forms of transportation globally. The aircraft's ability to mobilize between continents and its near-sound speed makes it an excellent cross-country travel choice. This paper discussed the production process of D-nose panel components for A-350 airplane wing in PT. Dirgantara Indonesia. PT. Dirgantara Indonesia (Persero) or commonly referred to as PTDI, is one of the aircraft companies in Asia with core competencies in aircraft design and development, aircraft structure manufacturing, aircraft production, and aircraft services for civil and military from light and medium aircraft. The main components of the aircraft consist of the engine, propeller (power plant), fuselage, wing, tail (empennage) and landing gear. The components that make up the wing of the aircraft consist of a fuel tank, wing flap, spar, aileron, skin, ribs, stringer, wingtip, as well as external parts such as the D-nose panel. The process from beginning to end of the D-nose panel component requires several stages. Finally, this process also checks data from existing component documents and ends with the final stamp as a sign that the entire process for making the D-nose panel component has been completed.